2021
DOI: 10.1002/vetr.1069
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic assessment of the completeness of arthroscopic subtotal coronoidectomy in dogs with medial coronoid disease

Abstract: Background: Until recent years, arthroscopic subtotal coronoidectomy has been the universally accepted treatment for medial coronoid disease but has variable clinical outcomes. The aim of this study was to evaluate the completeness of arthroscopic medial coronoid debridement and to detect the most vulnerable location of failure. Methods: Eighty-three dogs with a diagnosis of medial coronoid disease were included in the study. Arthroscopic debridement was performed in 92 elbow joints, and the completeness of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Of 29 dogs evaluated, 12 had calcified bodies, and 14 had scar tissue formation suspected secondary to the first arthroscopic procedure (31). In contrast, Renner et al (32) evaluated immediate or short-term postoperative CT scans for bony remnants and found that 73% of cases had remaining lesions, mostly at the radial incisure. That study reported that only 5% of radial incisure lesions were removed and 72% of apical lesions were removed completely.…”
Section: Discussionmentioning
confidence: 99%
“…Of 29 dogs evaluated, 12 had calcified bodies, and 14 had scar tissue formation suspected secondary to the first arthroscopic procedure (31). In contrast, Renner et al (32) evaluated immediate or short-term postoperative CT scans for bony remnants and found that 73% of cases had remaining lesions, mostly at the radial incisure. That study reported that only 5% of radial incisure lesions were removed and 72% of apical lesions were removed completely.…”
Section: Discussionmentioning
confidence: 99%
“…37 A more recent study reviewing 92 elbow joints on CT immediately following arthroscopic MCP fragment removal and subtotal coronoid osteotomy (SCO) revealed apical lesions to have been completely removed in 72% of cases but only 5% of radial lesions to have been completely debrided. 33 Nine percent of elbows had free bony remnants in the joint and 84% within the soft tissues of the previously placed instrument port. A fissured MCP rather than fragmentation was positively associated with an increased propensity for incomplete fragment removal.…”
Section: Mcp Fragment Removalmentioning
confidence: 96%
“…30 The use of 1.9 mm over 2.4/2.7 mm arthroscopes appear favored by some authors in more recent studies evaluating the elbow joint. [31][32][33] Arthroscopically assisted correction of axial humeroulnar incongruity has been described. 34 Acute adjustment via a proximal ulnar transverse osteotomy with a magnitude of adjustment based on arthroscopic measurement with a graduated hook probe was performed in four dogs with MCP fragments, when present, being removed concurrently.…”
Section: Arthroscopic Assessment Of Congruitymentioning
confidence: 99%
See 2 more Smart Citations